1999
DOI: 10.2223/jped.296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs in term infants with different degrees of acidemia in cord blood

Abstract: Nenhum critério, individualmente, tem a capacidade de distinguir, imediatamente após o nascimento, qual recém-nascido asfixiado exige cuidado em uma unidade de neonatologia. A definição de asfixia perinatal inclui, além dos critérios clínicos e o escore de Apgar 1 , também achados bioquímicos como acidemia, hipoxemia e hipercapnia 2 . O pH do sangue do cordão umbilical é o indicador mais sensível de sofrimento fetal, sendo acidemia definida como pH <7,20 no sangue da artéria umbilical 3,4 . Entre- ResumoObjet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The authors had found low correlation between clinical and laboratories parameters, with pH values to define asphyxia [11]. The same authors, in 1999, in research involving term neonates, also concluded that the Apgar bulletin less than 7 in the fifth minute, associated with the cord blood were not good indicators of evolution of organic failure [12].…”
Section: Discussionmentioning
confidence: 99%
“…The authors had found low correlation between clinical and laboratories parameters, with pH values to define asphyxia [11]. The same authors, in 1999, in research involving term neonates, also concluded that the Apgar bulletin less than 7 in the fifth minute, associated with the cord blood were not good indicators of evolution of organic failure [12].…”
Section: Discussionmentioning
confidence: 99%